Productivity and technological change in the sugarcane agribusiness in Mexico - Santiago Zárate, Ilich Miguel; Martínez Damián, Miguel Ángel; Cuevas Alvarado, Cristóbal Martín; Valdivia Alcala, Ramón; García Hernández, Mario Ivan; Hernández Toscano, Jesdel (Revista Mexicana de Ciencias Agrícolas, 2021)
The sugarcane agribusiness in Mexico is important due to its impact on employment and linkages in the economies of 267 municipalities of 15 states. The objective of this research was to analyze the total factor productivity, technical efficiency and technological change of sugarcane mills in Mexico. The method used was the Malmquist index, which measures changes in productivity over time and breaks it down into changes in efficiency and changes in technology under the assumptions of input orientation and constant returns to scale. The analysis used balanced panel data for the harvest period 2006/07-2015/16. The results show that at the level of decision-making units, the case of the El Dorado sugar mill in Sinaloa stands out, whose cumulative percentage change in its technical efficiency was 4.4%, in technical progress and innovation of 21.7% and a total productivity of the factors of 27%. The reverse situation occurs with the San Miguel del Naranjo sugar mill, whose cumulative percentage change in its technical efficiency grew by -10.20%, technological progress and innovation by -0.30% and its total factor productivity of -10.40%. The general conclusion is that for 20 sugar mills that operated in the study period, productivity grew at negative rates and for 30 it grew at positive rates.